2022
DOI: 10.1038/s41598-022-18523-y
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of a tannin-rich legume in the diet of beef steers reduces greenhouse gas emissions from their excreta

Abstract: The objectives of this study were to determine the emission of nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2), as well as the isotopic composition of N2O from excreta of beef steers fed ‘AU Grazer’ sericea lespedeza hay [SL; Lespedeza cuneata (Dum. Cours.) G. Don]. Fifteen Brahman × Angus crossbred steers were fed one of three experimental diets: 0, 50, or 100% inclusion of SL into ‘Tifton 85’ bermudagrass hay (Cynodon spp.). Gas sampling occurred on days 0, 1, 3, 5, 7, 14, 18, 25, and 32 after u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, it is suggested that year-round productivity should not underestimate the feeding value of forage resources containing secondary compounds (Ramıŕez-Restrepo and Charmley, 2015;Durmic et al, 2017;Vandermeulen et al, 2018b) to further reduce the impact on the C cycle by using the present fattening framework. This argument is strengthened by the counter-balancing effect of LWs and age targets on animal GHGE vs the reduction in GHGE from shorter fattening periods, especially considering not only that CP concentration in B. decumbens plus legumes swards can be 33% higher than in B. decumbens alone pastures (Rincoń and Villalobos, 2021) but also the effect of condensed tannins-containing legumes shifting N digestion and increasing fecal N concentration (Waghorn et al, 1987), thereby mitigating CH 4 , CO 2 , and N 2 O emission from excreta in the soil ( van Cleef et al, 2022), and increasing soil N retention in grazed pastures (Slebodnik, 2020).…”
Section: Estimated Production Patterns Methane Emissions and Carcass ...mentioning
confidence: 99%
“…Therefore, it is suggested that year-round productivity should not underestimate the feeding value of forage resources containing secondary compounds (Ramıŕez-Restrepo and Charmley, 2015;Durmic et al, 2017;Vandermeulen et al, 2018b) to further reduce the impact on the C cycle by using the present fattening framework. This argument is strengthened by the counter-balancing effect of LWs and age targets on animal GHGE vs the reduction in GHGE from shorter fattening periods, especially considering not only that CP concentration in B. decumbens plus legumes swards can be 33% higher than in B. decumbens alone pastures (Rincoń and Villalobos, 2021) but also the effect of condensed tannins-containing legumes shifting N digestion and increasing fecal N concentration (Waghorn et al, 1987), thereby mitigating CH 4 , CO 2 , and N 2 O emission from excreta in the soil ( van Cleef et al, 2022), and increasing soil N retention in grazed pastures (Slebodnik, 2020).…”
Section: Estimated Production Patterns Methane Emissions and Carcass ...mentioning
confidence: 99%
“…In this respect, the extracts of the following four pasture plants A. creticus , L. laxiflorus , C. incisum and T. repens have been determined to contain increased tannins, presumably as plant response to grazing pressures. In addition, an increased tannin diet of beef steers is determined to reduce considerably their excretions of greenhouse gases [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same authors found that the addition of tannins into Nellore bulls’ urine had an effect on the reduction in CH 4. OS van Cleef et al [ 64 ] also concluded that the inclusion of highly taniniferous plants effectively mitigated the emission of CH 4 in beef steers’ excreta.…”
Section: Antinutritional Factors Associated With Viscum ...mentioning
confidence: 99%